Perancangan dan Pembuatan Website UMKM Menggunakan Platform Webflow sebagai Media Promosi Digital - M Fatur Rahman; Fauziah Zulvios; Sularno Sularno; Zulfitri Yani (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Digital marketing has now become one of the key factors for micro, small, and medium enterprises (MSMEs) in promoting their products. This journal focuses on digital marketing strategies through Webflow for Queen Laundry MSME to enhance visibility and market penetration. The journal begins by providing context on the importance of digital marketing in the era of information and communication technology. In addition, this study explores the success of marketing through Webflow by examining website platforms relevant to Queen Laundry’s target market. The digital marketing methods through Webflow include creating an attractive website design, integrating customer testimonials, and implementing interactive and informative content strategies. Through the analysis of website traffic data, social media interactions, and customer data, this journal evaluates the effectiveness of these strategies in increasing online presence and customer engagement. The results of the study show that digital marketing through Webflow has a positive impact on brand awareness, consumer engagement, and customer loyalty improvement for Queen Laundry. This journal provides practical recommendations for Queen Laundry MSME to improve the effectiveness of digital marketing through Webflow, including enhancing content quality, developing relevant customer engagement strategies, and utilizing analytical data for better decision-making.